Neuro-linguistic proposal to potentiate voluntaryattention in students Colombians - Velasco Sinisterra, Hilda (2020)
The purpose of the research was to demonstrate the positive influence of the neurolinguistic programming proposal in the potential improvement of the voluntary attention of schoolchildren in public institutions in the urban area of ​​Buenaventura, Colombia. The methodology of this work is hypothetical deductive with an explanatory research level, the design in the study was experimental, with a quasi-experimental sub-design, longitudinal cut, where an evaluation pre-test was applied at the beginning of the academic cycle and a Post-test at the end, to two study groups divided as a control group and an experimental group, the strategy consisted of applying the neurolinguistic programming proposal to the experimental group to evaluate its effect and compare it with the control group. It was shown that there is a positive influence of the neurolinguistic programming proposal linked to learning styles in voluntary attention in transitional students in Buenaventura, Colombia.